Platelet phosphorylated TDP-43: an exploratory study for a peripheral surrogate biomarker development for Alzheimer's disease. (16th August 2017) - Wilhite, Rodger; Sage, Jessica M; Bouzid, Abdurrahman; Primavera, Tyler; Agbas, Abdulbaki
Aim: Alzheimer's disease (AD) and other forms of dementia create a noncurable disease population in world's societies. To develop a blood-based biomarker is important so that the remedial or disease-altering therapeutic intervention for AD patients would be available at the early stage.Materials & methods: TDP-43 levels were analyzed in postmortem brain tissue and platelets of AD and control subjects.Results: We observed an increased TDP-43 (<60%) in postmortem AD brain regions and similar trends were also observed in patient's platelets.Conclusion: Platelet TDP-43 could be used as a surrogate biomarker that is measurable, reproducible and sensitive for screening the patients with some early clinical signs of AD and can be used to monitor disease prognosis. Lay abstract: In this study, we explore to identify an Alzheimer's disease (AD)-selective phospho-specific antibody that recognizes the diseased form of TDP-43 protein in patient's blood-derived platelets. Our results suggest that selective antiphosphorylated TDP-43 antibody discriminates AD from non-demented controls and patients with amyotrophic lateral sclerosis. Therefore, platelet screening with a selective antibody could potentially be a useful tool for diagnostic purposes for AD.